Ka Amado - Reyes, Jun Cruz (Quezon City University of the Philippines Press, 2012)
Biography of Amado V. Hernandez, a Philippine writer and also a labor leader.
Keywords: Hernandez, Amado V. -- 1903-1970.; Hernandez, Amado V. -- 1903-1970 -- Criticism and interpretation; Authors, Filipino -- 20th century -- Biography; Authors, Filipino -- Biography